1987
DOI: 10.1002/anie.198705041
|View full text |Cite
|
Sign up to set email alerts
|

The Pyrolysis of Azides in the Gas Phase

Abstract: The chemistry of the non-metallic elements has in recent years passed through a period of rapid development, often referred to as its "renaissance". To emphasize just one of the key facets: numerous short-lived molecules containing multiple bonds to elements of the third and higher periods have been discovered, often accompanied by the planned synthesis of derivatives which are sterically shielded by bulky groups and thus kinetically stabilized. Thus today molecules such as silabenzenes HhC6-"Sin and silaethen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 146 publications
3
85
0
1
Order By: Relevance
“…22 The purity of 3 was checked by MS and nuclear magnetic resonance. The PES profile of 3 is very similar to those of CH 3 N 3 and CH 3 CH 2 N 3 which were reported previously, [11][12][13] and did not vary in different experiments.…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…22 The purity of 3 was checked by MS and nuclear magnetic resonance. The PES profile of 3 is very similar to those of CH 3 N 3 and CH 3 CH 2 N 3 which were reported previously, [11][12][13] and did not vary in different experiments.…”
Section: Methodssupporting
confidence: 86%
“…[11][12][13]23,24 The ionization energies corresponding to these two bands are 10.54 and 12.42 eV for CH 2 NH. Replacing one of the H atoms by a methyl group lowers the ionization energies to 9.20 and 11.20 eV in the case of CH 3 CHNH.…”
Section: ͑2͒mentioning
confidence: 99%
“…Detailed kinetic models on decomposition of EA included these species [23,24]. (CH 2 =NH) is the simplest imine compound, it has been observed in the pyrolysis of methylamine, ethylamine (amines in general), and azides as a reactive intermediate [25][26][27][28][29][30][31][32][33]. A great deal of research has been carried out to assign the microwave, infrared, and electronic spectrum of this moiety [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…(CH 2 =NH) is the simplest imine compound, it has been observed in the pyrolysis of methylamine, ethylamine (amines in general), and azides as a reactive intermediate [25][26][27][28][29][30][31][32][33]. A great deal of research has been carried out to assign the microwave, infrared, and electronic spectrum of this moiety [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. As a reactive species, MI can dissociate by 1,2-elimination of H 2 which has been studied both experimentally and theoretically [44][45][46][47][48][49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…This compound and its deuterated derivative (14, 15) have been the object of several detailed microwave spectrometry studies. In addition, a very recent photoelectron study (16) showed that the decomposition of trimethylenetetrazole yields N-cyanomethanimine and ethylene.…”
Section: Introductionmentioning
confidence: 99%